Classical biological control of the African citrus psyllid Trioza erytreae, a major threat to the European citrus industry - Pérez-Rodríguez, Jésica; Krüger, Kerstin; Pérez-Hedo, Mertixell; Ruiz-Rivero, Omar; Urbaneja, Alberto; Tena, Alejandro (Nature, 2019)
Citrus greening or huanglongbing (HLB) is the main threat to the European citrus industry since one of its vectors, the African citrus psyllid, Trioza erytreae, has recently become established in mainland Europe. In this context, classical biological control programmes should be implemented to reduce the spread of the psyllid. The aims of this study were to: i) disentangle the parasitoid complex of T. erytreae combining morphological and molecular characterization; and ii) to study the biology of its main parasitoids in its area of origin in South Africa for their future importation into Europe. The main citrus producing areas of South Africa were surveyed during 2017. In contrast to previous studies, the parasitoid complex of T. erytreae included three species of primary parasitoids: Tamarixia dryi, Psyllaephagus pulvinatus and another parasitoid of the genus Tamarixia. Molecular analysis showed that it is a new species closely related to T. dryi. Tamarixia dryi was the most abundant parasitoid but its relative abundance varied among sampling sites. The sex ratio (males/females) of T. dryi and Tamarixia sp. decreased with T. erytreae size and became female biased when psyllid nymphs were larger than 0.6 and 1.2 mm2, respectively. These parasitoids were attacked by three species of hyperparasitoids, Aphidencyrtus cassatus, Marietta javensis and a species of the genus Aphanogmus. Aphidencyrtus cassatus, the most abundant hyperparasitoid, tended to emerge from large nymphs, and adult females lived as long as those of T. dryi. The implications of these results are discussed within the framework of the introduction of T. dryi into Europe.